Avatrombopag improves thrombocytopenia in MYH9-related disorder following eltrombopag treatment failure. (17th November 2022) - Arif, Abdul Rehman; Zhao, Miaomiao; Chen, Wenlan; Xue, Mei; Luo, Shanshan; Wang, Yadan
Abstract: MYH9-related disorder (MYH9-RD) is autosomal dominant thrombocytopenia caused by mutations in the MYH9 gene, which codes for the non-muscle myosin-IIA heavy chain. We present a case of a 24-year-old Chinese man with MYH9-RD who was initially misdiagnosed with immune thrombocytopenia. Whole-exome sequencing and Sanger sequencing revealed a novel missense mutation in the MYH9 gene at the position of c.4550 G > T (p.G1517V) in exon 32. The same phenotype was observed in the proband, his mother, and his brother, in addition to macrothrombocytopenia and Dohle-like bodies in neutrophil granulocytes without non-hematologic manifestations. Following failed treatment with eltrombopag, avatrombopag, which was not mentioned before in the MYH9-RD treatment, was administered to the patient, and thrombocytopenia improved. In this case report, we present a novel pathogenic mutation and show the potential of avatrombopag for temporarily increasing the platelet count in patients with MYH9-RD.